A study of the role of the patient advocate as ‘a social support structure’, in HIV/AIDS medication adherence, in Dimbaza and Zwelitsha Clinics in the Province of the Eastern Cape, South Africa - Kamana, Nomfundo Lucy (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.